Non-Performing Micro, Small and Medium Enterprises Financing: Studies on Islamic Banking in Indonesia - Novianto, Abdullah Syakur Novianto; Rizal, Mohammad; Wahyuniar Asri, Nafadzila (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) have a very large role in the Indonesian economy, but they have the problem of not having access to capital from either banks or non-bank financial institutions. As a form of commitment to support government programs, conventional and Sharia banking extends credit to MSMEs. The amount of financing channelled by Sharia banking to the MSME sector has continued to increase, but the increase in MSME financing has had an impact on non-performing financing for MSME financing, which is above 5%. This study aims to determine the effect of financing margin, the financing-to-deposit ratio (FDR) and the inflation rate on non-performing financing (NPF) for MSME financing in Islamic banking in Indonesia. Multiple regression analysis is used in this study, and took a sample of 36 data was obtained from the financial services authority's Sharia banking statistical reports. This study found that the financing margin and the financing-to-deposit ratio (FDR) positively affect non-performing MSME financing. In contrast, the inflation rate does not affect non-performing MSME financing.